2021
DOI: 10.1016/j.molmet.2021.101196
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of ketohexokinase prevents fructose-induced metabolic dysfunction

Abstract: Objective Recent studies suggest that excess dietary fructose contributes to metabolic dysfunction by promoting insulin resistance, de novo lipogenesis (DNL), and hepatic steatosis, thereby increasing the risk of obesity, type 2 diabetes (T2D), non-alcoholic steatohepatitis (NASH), and related comorbidities. Whether this metabolic dysfunction is driven by the excess dietary calories contained in fructose or whether fructose catabolism itself is uniquely pathogenic remains controversial. We sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…Current approaches for a pharmacological treatment of NAFLD include the development of inhibitors targeting acetyl-CoA carboxylase and fatty acid synthase at the level of fatty acid synthesis, the mitochondrial pyruvate carrier, and ketohexokinase, a key enzyme in the metabolism of fructose, which is a particularly potent driver of de novo lipogenesis [ 52 , 53 ]. By demonstrating that regular exercise can antagonize the upregulation of these factors or reduce their expression in mice fed a steatogenic diet, our results corroborate these intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Current approaches for a pharmacological treatment of NAFLD include the development of inhibitors targeting acetyl-CoA carboxylase and fatty acid synthase at the level of fatty acid synthesis, the mitochondrial pyruvate carrier, and ketohexokinase, a key enzyme in the metabolism of fructose, which is a particularly potent driver of de novo lipogenesis [ 52 , 53 ]. By demonstrating that regular exercise can antagonize the upregulation of these factors or reduce their expression in mice fed a steatogenic diet, our results corroborate these intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of KHK activity with PF-06835919 is reported to prevent patients from hepatic steatosis, lipogenic, and fibrosis ( Shepherd et al, 2021 ). KHK deficiency or inhibition (PF-06835919) protects animals from fructose-induced obesity, insulin resistance, hypertriglyceridemia, and NAFLD ( Lanaspa et al, 2013 ; Futatsugi et al, 2020 ; Gutierrez et al, 2021 ). Knockout KHK could also decrease fructose-derived UA production and attenuate mitochondrial oxidative stress in mice ( Ishimoto et al, 2012 ).…”
Section: Possible Drug Targets In Fructose Metabolismmentioning
confidence: 99%
“…PF-06835919 represents a first-in-class selective KHK inhibitor to have entered clinical trials for the treatment of metabolic disorders and NAFLD/NASH (Futatsugi et al, 2020). In early clinical studies, PF-06835919 was found to be safe and well-tolerated in healthy study participants, and dose-dependently increased plasma fructose indicative of KHK inhibition (Gutierrez et al, 2021;Kazierad et al, 2021). The present study characterizes the transport and metabolic pathways involved in the hepatic clearance of PF-06835919, and thus understand the primary drivers to its clinical PK and target tissue exposure.…”
Section: Discussionmentioning
confidence: 99%
“…All PBPK model parameters and the data source are listed in Table 4. Based on the clinical PK data (Gutierrez et al, 2021), observed CL h,Human was approximated from oral CL (CL/F) across a dose range (10-600 mg) assuming oral absorption is complete and first-pass extract is negligible [i.e., CL h,Human = (Dose/AUC -renal CL) = 0.32 ± 0.04 mL/min/kg]. Direct scaling of metabolic clearance alone, CL int,app , underpredicted human oral clearance by about 3-fold (Figure 4).…”
Section: Human Pk Predictions Via Pbpk Based On In Vitro and Monkey S...mentioning
confidence: 99%
See 1 more Smart Citation